Variability in adenoma detection rate in control groups of randomized colonoscopy trials: a systematic review and meta-analysis - Hassan, Cesare; Piovani, Daniele; Spadaccini, Marco; Parigi, Tommaso; Khalaf, Kareem; Facciorusso, Antonio; Fugazza, Alessandro; Rösch, Thomas; Bretthauer, Michael; Mori, Yuichi; Sharma, Prateek; Rex, Douglas K.; et al. (Gastrointestinal endoscopy, 2023)
Adenoma detection rate (ADR) is still the main surrogate outcome parameter of screening colonoscopy, but most studies include mixed indications, and basic ADR is quite variable. We therefore looked at the control groups in randomized ADR trials using advanced imaging or mechanical methods to find out whether indications or other factors influence ADR levels. Patients in the control groups of randomized controlled trials (RCTs) on ADR increase using various methods were collected based on a systematic review; this control group had to use high-definition white-light endoscopy performed between 2008 and 2021. Random-effects meta-analysis was used to pool ADR in control groups and its 95% confidence interval (CI) according to clinical (indication and demographic), study setting (tandem/parallel, number of centers, sample size), and technical (type of intervention, withdrawal time) parameters. Interstudy heterogeneity was reported with the I2 statistic. Multivariable mixed-effects meta-regression was performed for potentially relevant variables. From 80 studies, 25,304 patients in the respective control groups were included. ADR in control arms varied between 8.2% and 68.1% with a high degree of heterogeneity (I2 = 95.1%; random-effect pooled value, 37.5%; 95% CI, 34.6‒40.5). There was no difference in ADR levels between primary colonoscopy screening (12 RCTs, 15%) and mixed indications including screening/surveillance and diagnostic colonoscopy; however, fecal immunochemical testing as an indication for colonoscopy was an independent predictor of ADR (odds ratio [OR], 1.6; 95% CI, 1.1-2.4). Other well-known parameters were confirmed by our analysis such as age (OR, 1.038; 95% CI, 1.004-1.074), sex (male sex: OR, 1.02; 95% CI, 1.01-1.03), and withdrawal time (OR, 1.1; 95% CI, 1.0-1.1). The type of intervention (imaging vs mechanical) had no influence, but methodologic factors did: More recent year of publication and smaller sample size were associated with higher ADR. A high level of variability was found in the level of ADR in the control groups of RCTs. With regards to indications, only fecal immunochemical test–based colonoscopy studies influenced basic ADR, and primary colonoscopy screening appeared to be similar to other indications. Standardization for variables related to clinical, methodologic, and technical parameters is required to achieve generalizability and reproducibility.